Islam Rahmatan lil’alamin and Social Media (Instagram & Tik-Tok Content Analysis Study) - karimah, Mia Fitriah El (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
The purpose of this article is to collect several references and discuss the influence of social media as a medium for campaigning regarding the Rahmatan lil’alamin Islamic movement. It will also discuss how Instagram and TikTok are used to promote the Islamic movement Rahmatan lil’alamin. This journal was prepared using a qualitative descriptive method that combines literature research on relevant sources and journals. A field study was used, focusing on Instagram and TikTok content. Islam Rahmatan lil’alamin is a religion that has the ability to create peace and compassion for both nature and humans if applied in people’s lives. There are many people all over the world who do good things for the universe. Rahmatan lil’alamin means compassion for the universe, and Islam means peace. So, what is meant by Islam Rahmatan lil’alamin is Islam that can bring peace and compassion to humans and nature. indeed emphasizes the values of goodness, peace and grace. However, Islam also recognizes that in some situations, firmness and fairness need to be applied. Islam has a balanced view of mercy and justice. Therefore, the Rahmatan lil’alamin Islamic movement campaign must be carried out massively and synergistically, especially throughout the world.